2013
DOI: 10.3390/mca18030340
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Heat Transfer Due to Twinjets Impingement onto an Isothermal Moving Plate

Abstract: Abstract-In this study, heat transfer from a moving isothermal hot plate due to double impinging vertical slot jets was investigated for a laminar flow. The rectangular geometry consists of a confining adiabatic wall placed parallel to the moving impingement. The jets are located symmetrically at mid point of upper wall. Water and Al 2 O 3 nanoparticles mixture with different volumetric fraction was used as working medium. In considered jet impingement problem, the effects of the jet exit Reynolds numbers, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Laminar convective heat transfer on an isothermal moving plate due to twin impinging slot jets with a nanofluid was reported by Başaran and Selimefendigil [25]. The results showed that the heat transfer increased with the plate velocity, Reynolds number, and the volumetric concentration of nanoparticles.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Laminar convective heat transfer on an isothermal moving plate due to twin impinging slot jets with a nanofluid was reported by Başaran and Selimefendigil [25]. The results showed that the heat transfer increased with the plate velocity, Reynolds number, and the volumetric concentration of nanoparticles.…”
Section: Introductionmentioning
confidence: 76%
“…The review noted that an impinging jet on a moving plate has been widely studied for different flow regimes and fluids, as highlighted in Table 1. However, apart from the works presented by Başaran and Selimefendigil [25] and Ersayın and Selimefendigil [26], the use of nanofluids in an impinging jet on a moving plate in a turbulent regime with nanofluids has not been fully addressed. It seems to the best of the authors' knowledge that there are no papers on an impinging jet with nanofluids on a moving plate in a turbulent regime.…”
Section: Introductionmentioning
confidence: 99%
“…From this aspect, with impinging jet, the flows are commonly used as a low-cost cooling method in various applications including heat treatment of metals, metal annealing, metal sheet fabrication, cooling the gas turbine blades, turbine seals, highdensity electronic chips, solar cells, internal combustion engines, drying the fabrics and paper, etc. [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The relations for splashing, however, were developed using droplets composed of pure fluids or fluid solutions. In the last decade, nanofluids, which are liquid dispersions containing nanoparticles with diameter less than 100 nm, have been proposed for a large number of applications as a way to enhance cooling with impinging jets [26][27][28], and sprays [3,[29][30][31] owing to their enhanced thermal properties. Nevertheless, no investigation has been performed to evaluate the impact of the nanofluids, and in particular of the nanoparticle load in the bulk fluid, on splashing.…”
Section: Introductionmentioning
confidence: 99%